2015
DOI: 10.1371/journal.pone.0143866
|View full text |Cite
|
Sign up to set email alerts
|

Historical Epidemics Cartography Generated by Spatial Analysis: Mapping the Heterogeneity of Three Medieval "Plagues" in Dijon

Abstract: ObjectivesThis work was designed to adapt Geographical Information System-based spatial analysis to the study of historical epidemics. We mapped "plague" deaths during three epidemics of the early 15th century, analyzed spatial distributions by applying the Kulldorff's method, and determined their relationships with the distribution of socio-professional categories in the city of Dijon.Materials and MethodsOur study was based on a database including 50 annual tax registers (established from 1376 to 1447) indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…The historical literature on Italian and European late medieval and early modern plagues seems to have clearly established that, in contrast to the Black Death and other early plague waves, the disease acquired a social character from the fifteenth century, striking the poor preferentially (Slack 1985;Alfani 2009Alfani , 2013bCohn 2010b). This has been confirmed by recent studies of specific plague outbreaks (Galanaud et al 2015;Whittles and Didelot 2016). Doctors of the early modern period were of the same view (Cohn 2010a).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The historical literature on Italian and European late medieval and early modern plagues seems to have clearly established that, in contrast to the Black Death and other early plague waves, the disease acquired a social character from the fifteenth century, striking the poor preferentially (Slack 1985;Alfani 2009Alfani , 2013bCohn 2010b). This has been confirmed by recent studies of specific plague outbreaks (Galanaud et al 2015;Whittles and Didelot 2016). Doctors of the early modern period were of the same view (Cohn 2010a).…”
Section: Discussionmentioning
confidence: 55%
“…The same was found by Cohn and Alfani (2007) for Milan in 1523. For Dijon in 1400 and 1428, Galanaud et al (2015) found that plague had more effect on the richest parts of the city, where most commercial and craft activities were concentrated (as they argue, 'In a city where garbage collection was left to the inhabitants, the proximity of food stocks, crop market, second-hand clothing dealers … and/or an open area used for slaughter … created conditions suitable for rats to pullulate and favored disease transmission by fleas' (p. 20)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, we are not sure that the mentions of plague identified originally by Biraben were in fact plague at all, especially for the medieval period, and as mentioned, we have no way of checking Biraben’s data set without citations to the original manuscripts. This problem is further illuminated by some of the plagues Biraben identified, such as the plague of 1437–1440, which occurred during a period of extreme cold weather ( 35 , 36 ) and manifested as harvest failures and famine-related diseases ( 37 ); research has suggested that waterborne infections were more likely the cause of this pestilence ( 38 ). …”
Section: Biraben Data Setmentioning
confidence: 99%
“…However, the results of different studies (e.g. DeWitte, 2010b; Galanaud et al, 2015;Crespo, Lawrenz, 2016) have shown that this is not the case, but rather, that susceptibility to death varies during sudden events such as epidemics, which have been referred to as heterogeneity in frailty (Wood et al, 1992). Recent research has indicated that one of the worst demographic crises, the Black Death, caused selective mortality and removed the frailest of the population (DeWitte, 2016).…”
mentioning
confidence: 99%